Pneumomediastinum Following Acute Cough - Bajracharya, Sumana (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Spontaneous pneumomediasinum a relatively uncommon entitity. It is usually seen in young and pregnant women. Management includes close observation and supportive management. We report a case of 22 years old male presenting with shortness of breath following acute cough. His clinical finding was suggestive of subcutaneous emphysema. CT scan revealed pneumonediastineum. The patient was admitted and observed for 3 days and was discharged on third day after resolution of his symptoms.